Post-election performance of political parties in Ghana’s Fourth Republic - Joseph Kofi Agyapong Darmoe; Kingsley Agomor; Kwaku Obeng Effah (Cogent Social Sciences, 2024)
The dominant literature on performance of political parties seems to suggest that African parties are not agents of democracy. The article examines the performance of political parties in Ghana. A cross-sectional study was adopted based on a national sample survey across 10 administrative regions of Ghana. Data were collected from citizens of voting age based on the functional approach suggested in the literature. The article finds that Ghana’s political parties are effective in performing the following functions: mobilization of voters during elections, training national leaders, and formulating and implementing public education on government policies and programmes. The findings further indicate that political parties, especially the opposition parties, frequently perceived their role as potential governments-in-waiting. In this capacity, they ensure accountable governance by assuming a ‘watchdog’ role over the ruling administration. The article challenges the notion that political parties in Africa are generally weak in their functionalities, instead demonstrating that Ghana’s political parties have played a pivotal role in democratic development despite their limitations.